O FINANCIAMENTO DA EDUCAÇÃO EM CONTEXTOS FEDERATIVOS DO BRASIL, DA ARGENTINA E DO MÉXICO: RELAÇÕES INTERGOVERNAMENTAIS PARA A GARANTIA DA ETAPA OBRIGATÓRIA DE ESCOLARIZAÇÃO - Silva, Patricia Luzorio Marques da (2022)
The paper research was developed with the objective of comparing the education financing in the federative contexts of Brazil, Argentina, and Mexico and how they guarantee the compulsory stage of schooling with basis for intergovernmental relations. The t